Measuring public-involving economic crime: A case study in Beijing, China - Peng, Xinlin (International journal of law, crime and justice, 2021)
Public-involving economic crime refers to economic crimes that use false propaganda to obtain money or other valuable items from multiple, unspecific victims in the Chinese context. Based on the Beijing public-involving economic crime cases from 2012 to 2018, this study analyses the operation features and effects of public-involving economic crimes. We find that the intersection in criminal and civil procedures, inefficient property preservation, repeat prosecution, and inappropriate information disclosure remain the major judicial dilemmas of public-involving economic crimes. We examine the causes of public-involving economic crimes from the opportunity perspective. Lack of effective regulation and inadequate financial literacy among investors creates opportunities that offenders can easily exploit. This study suggests that practical administrative efforts such as continuous supervision of market entities’ economic activities and financial literacy education can block crime opportunities and prevent public-involving economic crimes.